Method for controlling influence of ore distribution sequence on air permeability of material layer
By detecting and optimizing the ore fabric sequence under high pellet ore ratio, the airflow and furnace condition deterioration caused by pellet ore rolling towards the center and edge of the blast furnace are solved, and the air permeability of the material layer and the improvement of blast furnace smelting level are achieved.
Patent Information
- Application Number
- CN202411893761.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
Under high pellet ore ratio, pellet ore tends to roll towards the center and edge of the furnace wall, resulting in weakening of the airflow in the center and edges. Long-term operation will lead to deterioration of the furnace condition and poor air permeability of the furnace.
The air permeability of the furnace material structure of ore + coke of different ore fabric orders was detected under a reducing atmosphere of 500°C to 1600°C, and the fabric order was optimized according to the detection results to improve the breathability of the material layer.
The ore fabric sequence is optimized, the reasonable distribution of gas flow in the blast furnace is improved, the long-term stable and forward movement of the blast furnace is ensured, and the permeability of the furnace material and the blast furnace smelting level are improved.
Smart Images

Figure CN119614774A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ironmaking, and more specifically, relates to a method for controlling the influence of ore distribution sequence on the air permeability of a material layer under high pellet ratio. Background Art
[0002] Pelletized ore is a spherical artificial iron ore made by mixing fine concentrate powder and other additives, adding water and rolling them into balls on a pelletizing machine, and then drying and high-temperature roasting to consolidate. Its main components include SiO2, Al2O3, CaO, MgO, TFe, Mn, P, S, etc., as well as a small amount of K2O, Na2O, FeO, Ni and other elements. In the blast furnace ironmaking process, revealing the ore distribution order is of great significance to optimizing production efficiency. For the ironmaking process, in order to ensure the stability of the ironmaking process, it is necessary to control the limited distribution order of the raw materials involved in the blast furnace, such as sintered ore and pelletized ore, which is of great significance to the distribution of blast furnace gas flow. In recent years, with the development of high-ball ratio smelting technology in blast furnaces, the proportion of pellets entering the furnace has been further improved. However, due to the characteristics of uniform particle size, small natural pile angle, and easy rolling of pellets, the pellets are easy to roll to the center of the blast furnace and the edge of the furnace wall, resulting in weakening of the center and edge airflow. Long-term operation will lead to the deterioration of the furnace condition and the thickening of the furnace wall. The large difference in charge particle size causes an increase in the proportion of the charge mixed layer and an increase in the interface effect, resulting in poor charge permeability and an increase in the blast furnace pressure difference. After the pellets roll to the center, the center airflow is suppressed and the edge airflow is easy to develop. These factors have led to the gradual irrationality of the distribution of the two gas flows in the blast furnace.
[0003] Chinese patent application CN109022649B discloses a blast furnace charging method and device, the method comprising: determining the batch weight of each charge, the charge comprising: coke and ore; placing the charge into the blast furnace in sequence according to a pre-set charging sequence and a charging matrix corresponding to each charge; wherein the pre-set charging sequence comprises: large coke, small-particle sintered ore, large-particle sintered ore + small coke; the particle size of the large coke is greater than 25 mm, the particle size of the small coke is 12-25 mm, the particle size of the large-particle sintered ore is greater than 11 mm, and the particle size of the small-particle sintered ore is 4-11 mm.
[0004] Chinese patent application CN114085938A discloses a process for smelting limestone-type fluorine-containing flux pellets under high ball ratio conditions in a large blast furnace, comprising the following steps: sintered ore, limestone-type fluorine-containing flux pellets, acidic pellets, coke and silica are separately loaded into a receiving trough, and then the proportion of the four materials is controlled by controlling the process parameters of the vibrating screen and batching facilities on the receiving trough, each material is discharged into a feeding belt according to a predetermined proportion, and then transported to the receiving ore trough on the furnace top; the loading amount of the materials includes: ore batch weight of 47-50t / batch, coke batch weight of 12.0-13.0t / batch, and silica batch weight of 0-0.6t / batch; the iron material proportion of the ore batch is controlled as follows: the proportion of sintered ore is 45%~50%, the proportion of acidic pellets is 15%-20%, and the proportion of limestone-type fluorine-containing flux pellets is 30%~35%. This method determines the suitable 2 Operation system for smelting limestone-type fluorine-containing flux pellets under high pellet ratio conditions in blast furnace.
[0005] The above existing technologies only involve a certain specific distribution sequence, which is not suitable for matching the optimal distribution sequence for different pellet ratios. Therefore, the distribution sequence of iron ore used in actual blast furnace production and its distribution position in the blast furnace have a profound impact on the gas flow distribution. Summary of the invention
[0006] In view of this, the present invention proposes a method for controlling the influence of ore feeding sequence on the permeability of the material layer under high pelletizing ratio, aiming to improve the ore feeding sequence, optimize the reasonable distribution of ore in the blast furnace, develop two internal airflows at the center and edge, and ensure the long-term stable and smooth operation of the blast furnace.
[0007] In order to solve at least one of the above technical problems, the present invention adopts the following technical solution: According to the present invention, a method for controlling the effect of ore distribution sequence on the permeability of the material layer under high pellet ratio is provided, comprising: step S100, detecting the permeability of the charge structure of ore+coke with different ore distribution sequences under a reducing atmosphere of 500°C~1600°C; step S200, optimizing the distribution sequence according to the detection result. Wherein, in terms of volume percentage, the reducing atmosphere comprises 0~100% CO+0~100% H2+0~99% N2.
[0008] According to one embodiment of the present invention, in step 100, the charge is subjected to a soft melting dripping test in a reducing atmosphere at 500°C to 1600°C, and the quality of the air permeability is judged based on the obtained S characteristic value.
[0009] According to one embodiment of the present invention, the charge structure of ore+coke is an "upper coke+ore+lower coke" structure.
[0010] According to one embodiment of the present invention, the particle size of coke is 10 mm to 12.5 mm, and the particle size of ore is 10 mm to 12.5 mm.
[0011] According to one embodiment of the present invention, the ore comprises, by mass percentage, 50% to 99% pellets and 1% to 50% sintered ore.
[0012] According to one embodiment of the present invention, the middle ore layer of the "upper coke + ore + lower coke" structure is charged with a mixture of sintered ore and pelletized ore in different distribution orders.
[0013] According to one embodiment of the present invention, the mixed charging in different distribution sequences includes: charging the sintered ore and the pelletized ore in a left-right distribution type furnace charge structure.
[0014] According to one embodiment of the present invention, the mixed loading in different distribution sequences includes: loading pellets at the top and sintered ore at the bottom.
[0015] According to one embodiment of the present invention, the mixing and charging in different distribution sequences includes: charging after mixing the sintered ore and the pelletized ore.
[0016] According to one embodiment of the present invention, the mixed loading in different distribution sequences includes: loading sintered ore at the top and pelletized ore at the bottom.
[0017] By adopting the above technical scheme, compared with the prior art, the present invention proposes a method for controlling the permeability of the material layer by the order of ore distribution based on the charge structure with a high proportion of pellet ore into the furnace (≥50%) (50%~99% pellet ore + 1%~50% sintered ore), which solves the problem that the permeability of the blast furnace cannot be accurately and objectively evaluated under the material layer structure under the condition of the single order of distribution in the existing blast furnace production, thereby optimizing the order of ore distribution based on the permeability of the blast furnace and improving the reasonable distribution of the two gas flows. Applying the method according to the present invention to the production practice of the blast furnace is conducive to the refined operation of the charge, optimizing the order of distribution, reducing the resistance of the upward movement of the gas flow, improving the permeability of the charge, strengthening the smelting level of the blast furnace, and improving the stability of the blast furnace operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0019] Figure 1A flow chart showing a method for controlling the effect of ore distribution sequence on the permeability of a material layer under a high pellet ratio according to an embodiment of the present invention is shown; Figure 2 A schematic diagram of a furnace charge structure according to an embodiment of the present invention is shown; Figure 3 The pressure difference and S characteristic value of the charge structure soft melting dripping process according to Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0020] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0021] It should be understood that the embodiments of the present invention shown in the exemplary embodiments are only illustrative. Although only a few embodiments are described in detail in the present invention, it is easy for those skilled in the art to appreciate that multiple modifications are feasible without actually departing from the teaching of the subject matter of the present invention. Accordingly, all such modifications should be included within the scope of the present invention. Without departing from the gist of the present invention, other replacements, modifications, changes and deletions may be made to the design, operating conditions and parameters of the following exemplary embodiments.
[0022] In addition, reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0023] like Figure 1 As shown, according to a method for controlling the influence of ore distribution sequence on the air permeability of a material layer under a high pellet ratio of the present invention, the method generally comprises the following steps: Step S100, testing the air permeability of the charge structure of ore+coke in different ore distribution sequences under a reducing atmosphere at 500° C. to 1600° C., in terms of volume percentage, wherein the reducing atmosphere comprises 0-100% CO+0-100% H2+0-99% N2; Step S200, optimizing the order of laying out materials according to the detection result.
[0024] The present invention proposes a method for controlling the permeability of the material layer by the order of ore distribution based on the charge structure (50%~99% pellets + 1%~50% sintered ore) with a high proportion of pellets (≥50%). The charge structure of ore + coke in step S100 is preferably an "upper coke + ore + lower coke" structure. Among them, the middle ore layer (sintered ore or pellets) is mixed together for charging, and the permeability of the charge is greatly affected by the order of ore distribution, and the relationship of the order of ore distribution is comprehensively considered.
[0025] In step S100, the charge can be subjected to a soft melting dripping test under a reducing atmosphere at 500°C to 1600°C, and the permeability is judged based on the obtained S characteristic value. The soft melting dripping test simulates the temperature, atmosphere and charge structure in the blast furnace, places the iron-containing raw material in an experimental device, and heats it to a high temperature state. In an embodiment of the present invention, the reducing atmosphere contains 0~100%CO+0~100%H2+0~99%N2 by volume percentage. During the experiment, the raw material will gradually soften, melt, and eventually drip into the collector below the device. By observing and recording the soft melting and dripping process of the raw material, its soft melting dripping performance can be evaluated, including characteristic parameters such as soft melting start temperature, dripping start temperature, and maximum pressure difference. In the soft melting dripping experiment, the S characteristic value refers to the numerical representation of specific parameters or indicators related to the soft melting and dripping performance of the raw material, such as the soft melting start temperature, the dripping start temperature, the soft melting interval, the dripping rate, the maximum pressure difference, and the permeability index. Among them, the maximum pressure difference is the maximum pressure difference between the upper and lower raw material layers during the experiment, which can reflect the permeability of the raw materials during the soft melting and dripping process. The present invention judges the permeability of the charge structure with different ore distribution sequences based on the S characteristic value corresponding to the maximum pressure difference obtained in the soft melting dripping experiment, that is, the smaller the S characteristic value, the better the permeability of the material layer.
[0026] During the soft melting dripping experiment, the finer the ore particle size, the larger its specific surface area, and the increased contact area with the reaction gas, thereby accelerating the reaction speed and facilitating the soft melting dripping process; too fine a particle size may lead to decreased permeability, because fine particles are more likely to form a compact stacking structure, affecting gas circulation. In the embodiment of the present invention, the coke particle size is preferably 10 mm to 12.5 mm, and the ore particle size is preferably 10 mm to 12.5 mm.
[0027] In the embodiment of the present invention, the middle ore layer of the "upper coke + ore + lower coke" structure is charged with sintered ore and pelletized ore in different order of distribution. Figure 2As shown, the materials are mixed and charged in different charging sequences, including: A) charging with a left-right distribution type charge structure of sintered ore and pelletized ore; B) charging with pelletized ore at the top and sintered ore at the bottom; C) charging with sintered ore and pelletized ore after mixing; D) charging with sintered ore at the top and pelletized ore at the bottom. Those skilled in the art can design more types of charging sequences according to actual working conditions.
[0028] The following is a specific embodiment of the method for controlling the effect of ore distribution sequence on the permeability of the material layer under high pellet ratio according to the present invention and its specific process parameters.
[0029] Example 1 This embodiment is a method for controlling the effect of ore distribution sequence on the permeability of the material layer under a charge structure of 55% pelletized ore + 45% sintered ore.
[0030] Step S100, testing the air permeability of the charge structure of ore+coke with different ore distribution sequences under a reducing atmosphere at 1000°C.
[0031] Specifically, the charge was subjected to a soft melting dripping experiment under a reducing atmosphere (50% CO + 30% H2 + 20% N2) from low temperature to high temperature. 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke, 225g of sintered ore with a particle size of 10mm~12.5mm, and 275g of pelletized ore with a particle size of 10mm~12.5mm were added, and the total mass of the ore layer was 500g. Figure 2 The four charge structures A, B, C and D shown are respectively loaded into crucibles with an inner diameter of 75 mm, and the thickness of the charge layer is about 60 mm.
[0032] Step S200, optimizing the order of laying out materials according to the detection result.
[0033] Specifically, the pressure difference and S characteristic value under each material layer structure after the soft melt dripping experiment are as follows: Figure 3 As shown. The results show that the maximum pressure differences under the four material layer structures A, B, C, and D are 12.62kPa, 17.01kPa, 15.68kPa, and 16.07kPa, respectively, and the corresponding S characteristic values are 557.62kPa•℃, 708.43kPa•℃, 719.92kPa•℃, and 1603.51kPa•℃, respectively. It can be seen that the air permeability under the material layer structure A is the best, followed by the material layer structure B, and the air permeability under the material layer structure D is the worst. Therefore, in terms of the air permeability of the material layer, the material layer structure A is preferred when laying the charge under the charge structure of 55% pellet ore + 45% sintered ore.
[0034] Example 2 This embodiment is a method for controlling the effect of ore distribution sequence on the permeability of the material layer under a charge structure of 60% pelletized ore + 40% sintered ore.
[0035] Step S100, testing the air permeability of the charge structure of ore+coke with different ore distribution sequences under a reducing atmosphere at 800°C.
[0036] Specifically, the charge was subjected to a soft melting dripping experiment under a high temperature reducing atmosphere (90% CO + 5% H2 + 5% N2). 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke, 200g of sintered ore with a particle size of 10mm~12.5mm, and 300g of pelletized ore with a particle size of 10mm~12.5mm were added. The total mass of the ore layer was 500g. Figure 2 In the four loading methods A, B, C and D, the ore is loaded into a crucible with an inner diameter of 75 mm, and the material layer thickness is about 60 mm.
[0037] Step S200, optimizing the order of laying out materials according to the detection result.
[0038] Specifically, the pressure difference and S characteristic value under each material layer structure were obtained after the soft melting dripping experiment. The order of material distribution was optimized according to the experimental results. The results showed that in terms of material layer permeability, material layer structure A was preferred when distributing materials under the charge structure of 60% pellet ore + 40% sintered ore.
[0039] Example 3 This embodiment is a method for controlling the effect of ore distribution sequence on the permeability of the material layer under a charge structure of 80% pelletized ore + 20% sintered ore.
[0040] Step S100, testing the air permeability of the charge structure of ore+coke with different ore distribution sequences under a reducing atmosphere (10% CO+80% H2+10% N2) at 1600°C.
[0041] Specifically, the charge was subjected to a soft melting dripping experiment under a high temperature reducing atmosphere. 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke, 200g of sintered ore with a particle size of 10mm~12.5mm, and 300g of pelletized ore with a particle size of 10mm~12.5mm were added, and the total mass of the ore layer was 500g. Figure 2 In the four loading methods A, B, C and D, the ore is loaded into a crucible with an inner diameter of 75 mm, and the material layer thickness is about 60 mm.
[0042] Step S200, optimizing the order of laying out materials according to the detection result.
[0043] Specifically, the pressure difference and S characteristic value under each material layer structure were obtained after the soft melting dripping experiment. The order of material distribution was optimized according to the experimental results. The results showed that in terms of material layer permeability, material layer structure A was preferred when distributing materials under the charge structure of 60% pellet ore + 40% sintered ore.
[0044] Example 4 This embodiment is a method for controlling the effect of ore distribution sequence on the permeability of the material layer based on a charge structure of 95% pelletized ore + 5% sintered ore.
[0045] Step S100, testing the air permeability of the charge structure of ore+coke with different ore distribution sequences under 500 reducing atmosphere (90% CO +10% N2).
[0046] Specifically, the charge was subjected to a soft melting dripping experiment under a high temperature reducing atmosphere. 30g of upper coke with a particle size of 10mm~12.5mm, 30g of lower coke, 200g of sintered ore with a particle size of 10mm~12.5mm, and 300g of pelletized ore with a particle size of 10mm~12.5mm were added, and the total mass of the ore layer was 500g. Figure 2 In the four loading methods A, B, C and D, the ore is loaded into a crucible with an inner diameter of 75 mm, and the material layer thickness is about 60 mm.
[0047] Step S200, optimizing the order of laying out materials according to the detection result.
[0048] Specifically, the pressure difference and S characteristic value under each material layer structure were obtained after the soft melting dripping experiment. The order of material distribution was optimized according to the experimental results. The results showed that in terms of material layer permeability, material layer structure A was preferred when distributing materials under the charge structure of 60% pellet ore + 40% sintered ore.
[0049] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0050] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for controlling the effect of ore distribution sequence on the air permeability of the material layer. A method for controlling the effect of ore distribution sequence on the air permeability of the material layer under high pellet ratio, characterized in that: include: Step S100, testing the air permeability of the charge structure of ore+coke in different ore distribution sequences under a reducing atmosphere at 500° C. to 1600° C., in terms of volume percentage, wherein the reducing atmosphere comprises 0-100% CO+0-100% H2+0-99% N2; Step S200, optimizing the order of laying out materials according to the detection result.
2. The method according to claim 1, characterized in that: In the step S100, the charge is subjected to a soft melting dripping test in a reducing atmosphere at 500°C to 1600°C, and the quality of the air permeability is judged based on the obtained S characteristic value.
3. The method according to claim 2, characterized in that The charge structure of ore+coke is an "upper coke+ore+lower coke" structure.
4. The method according to claim 3, characterized in that The particle size of coke is 10mm~12.5mm, and the particle size of ore is 10mm~12.5mm.
5. The method according to claim 3, characterized in that: In terms of mass percentage, the ore comprises 50% to 99% pellets and 1% to 50% sintered ore.
6. The method according to claim 5, characterized in that The middle ore layer of the "upper coke + ore + lower coke" structure is charged with a mixture of sintered ore and pelletized ore in different distribution orders.
7. The method according to claim 6, characterized in that The mixed charging in different distribution sequences includes: charging of sintered ore and pelletized ore in a left-right distribution type furnace charge structure.
8. The method according to claim 6, characterized in that The mixed loading in different material distribution sequences includes: loading pellets at the top and sintered ore at the bottom.
9. The method according to claim 6, characterized in that The mixing and charging in different distribution sequences includes: charging after the sintered ore and the pelletized ore are mixed evenly.
10. The method according to claim 6, characterized in that The mixed loading in different distribution sequences includes: loading sintered ore at the top and pelletized ore at the bottom.
Citation Information
Patent Citations
A method and apparatus for charging blast furnaces
CN109022649B
Process for smelting limestone type fluorine-containing fluxed pellets in large blast furnace under high pellet ratio condition
CN114085938A